Patellar taping for patellofemoral pain: a systematic review and meta-analysis to evaluate clinical outcomes and biomechanical mechanisms - Barton, C.; Balachandar, V.; Lack, S.; Morrissey, D. (British Journal of Sports Medicine, 2014)
Objective: Patellar taping is frequently used to treat patellofemoral pain (PFP). This systematic review and meta-analysis (1) evaluates the efficacy of patellar taping for patients with PFP, (2) compares the efficacy of various taping techniques and (3) identifies potential biomechanical mechanisms of action. Methods: The MEDLINE, CINAHL, SPORTSDiscus, Web of Science and Google Scholar databases were searched in January 2013 for studies evaluating the effects of patellar taping on pain and lower-limb biomechanics in individuals with PFP. Three independent reviewers assessed each paper for inclusion and two assessed for quality. Means and SDs were extracted from each included study to allow effect size calculations. Results: Twenty studies were identified. There is moderate evidence that (1) tailored (customised to the patient to control lateral tilt, glide and spin) and untailored patellar taping provides immediate pain reduction of large and small effect, respectively and (2) tailored patellar taping promotes earlier onset of vastus medialis oblique (VMO) contraction (relative to vastus lateralis contraction). There is limited evidence that (1) tailored patellar taping combined with exercise provides superior pain reduction compared to exercise alone at 4 weeks, (2) untailored patellar taping added to exercise at 3-12 months has no benefit and (3) tailored patellar taping promotes increased internal knee extension moments. Conclusions: Tailoring patellar taping application (ie, to control lateral tilt, glide and spin) to optimise pain reduction is important for efficacy. Evaluation of tailored patellar taping beyond the immediate term is limited and should be a research priority. Possible mechanisms behind patellar taping efficacy include earlier VMO onset and improved knee function capacity (ie, ability to tolerate greater internal knee extension moments).